Attitudes, motivations and behaviors of adolescents who are ready for games-related careers - Meesang, Chutima; เกียรติรุ่งฤทธิ์ คมสันต์; มุสิกพันธ์ วิมลทิพย์; Atsariyasing, Wanlop (NU Journal of Nursing and Health Sciences, 2023)
This descriptive research aimed to study the attitudes, motivations, and behaviors of adolescents who are ready for games-related careers. The data were collected by in-depth interviewing adolescents aged 13 to 18 and their parents, using semi-structured interviews. The obtained data were analyzed by using content analysis for qualitative data. The interviews were conducted between May and June 2022.This research has been certified by the MU-MOU Institutional Review Board (IRB3) under certification number 170/2565. The results showed that the informants’ attitudes towards games-related careers were three different aspects: these were 1) job insecurity, instable salary, being only an alternative way to make money, 2) sustainable career, continuity of salary, opportunity depending on self-capacity, and 3) being a job expected to growth in the future. Motivations were: 1) desire of playing games, 2) work flexibility and comfortability, 3) challenges to prove self-capacity, 4) influences of media, 5) desire of being as an idol, 6) being accepted by others, 7) salary, and 8) opportunity for other games-related careers. Different well-prepared behaviors for games-related careers were divided into three groups including those with, i.e., 1) basic knowledge, 2) some experiences and skills with current career-related activities as hobbies, and 3) some experiences and skills without such hobbies at the present. In conclusion, the behavior of well-preparation for games-related careers among the adolescents has several processes. In each step of the process, a person is required to be disciplined, responsible, and acknowledgeable. The person should continue learning and have a second plan for other simultaneous careers together with good family support and adequate relevant tools.